A Digital Treasure Trove for Portuguese Legal History - Camarinhas, Nuno (2022)
In the past few years, major resources have become available for researchers of Portuguese legal history. In this context, António Manuel Hespanha played a pioneering role; he was responsible for creating the first online digital library on Portuguese and colonial legal texts, hosted by the NOVA School of law ( https://novalaw.unl.pt/arquivo-digital-antonio-manuel-hespanha). Here, the user has access to a curated collection of books on doctrinal works, draft legislation, parliamentary debates, legislative pieces, and jurisprudence, mainly covering the constitutional period and the liberal reformations that took place after the 1820 revolution. Inspired by Hespanha’s aim to create accessible collections of sources, two other projects focused on legislation from the early modern and modern periods: Ius Lusitaniae and, more recently, O Governo dos Outros, which integrated the data from the former and extended the chronological scope to the Portuguese colonial experience ( http://www.governodosoutros.ics.ul.pt). In the same vein, and building on previous experience with these projects, LEGALPL – Legal Pluralism in the Portuguese Empire (18th–20th centuries) ( https://pluralismojuridiconoimperio.fd.unl.pt/), promises to further expand on the digitization of colonial legislation.